2009
DOI: 10.1007/s10544-009-9389-2
|View full text |Cite
|
Sign up to set email alerts
|

Glass-composite prototyping for flow PCR with in situ DNA analysis

Abstract: In this article, low cost microfluidic devices have been used for simultaneous amplification and analysis of DNA. Temperature gradient flow PCR was performed, during which the unique fluorescence signature of the amplifying product was determined. The devices were fabricated using xurography, a fast and highly flexible prototype manufacturing method. Each complete iterative design cycle, from concept to prototype, was completed in less than 1 h. The resulting devices were of a 96% glass composition, thereby po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The combination of two single reactions into one microfluidic reactor represents high system integration in comparison to other publications (Sun et al 2008;Hartung et al 2009). In contrast to prototype devices (Pjescic et al 2010;Ramalingam et al 2010), the established fabrication method is capable of large-scale production, which is crucial when used as disposable device. Furthermore, this potential to dispose the chip after the analysis is crucial, when the chip should be used as an IVD test.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of two single reactions into one microfluidic reactor represents high system integration in comparison to other publications (Sun et al 2008;Hartung et al 2009). In contrast to prototype devices (Pjescic et al 2010;Ramalingam et al 2010), the established fabrication method is capable of large-scale production, which is crucial when used as disposable device. Furthermore, this potential to dispose the chip after the analysis is crucial, when the chip should be used as an IVD test.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the amplification of phage DNA (Pjescic et al 2010;Dorfman et al 2005) or abundant DNA templates (Obeid et al 2003), this approach is applicable to the detection of minute amounts of pathogenic bacteria. Furthermore a reduced sensitivity compared to conventional thermocyclers (Sauer-Budge et al 2009;Park et al 2003) was not observed using our microfluidic device.…”
Section: Limit Of Detectionmentioning
confidence: 99%
“…Most literature demonstrate a proof of principle without concentrating on the limits and drawbacks important for a particular application. The major constraints are the restriction to phage DNA (Pjescic et al 2010;Dorfman et al 2005), limited amplicon lengths (Mahalanabis et al 2010;Zhang and Xing 2010;Li et al 2009), lower sensitivity compared to conventional thermocyclers (Sauer-Budge et al 2009;Park et al 2003) and the restriction to abundant DNA templates (Obeid et al 2003). In aspect of species identification by DNA microarrays, long targets are especially important for the accurate discrimination between different bacteria (Wiesinger-Mayr et al 2007;Yu et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Typically, an additional postprocessing step that takes about 30 min is required by existing NAT devices to obtain melt curves. Previously, we have reported the acquisition of amplification and melt curves using fluorescence images while thermocycling the sample (Crews, Wittwer, & Gale, 2008; Crews, Wittwer, Montgomery, Pryor, & Gale, 2009; Pjescic & Crews, 2012; Pješčić, Tranter, Hindmarsh, & Crews, 2010). This system was based on continuous flow in a thermal gradient, eliminating the need for stringent temperature control.…”
Section: Introductionmentioning
confidence: 99%